2018
DOI: 10.3389/fnbeh.2018.00094
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation, Symptomatology, and Cognition in Psychosis: A Qualitative Review

Abstract: Schizophrenia is a chronic, debilitating condition that affects approximately 1% of the population. Individuals diagnosed with schizophrenia typically exhibit positive (e.g., hallucinations) and negative symptoms (e.g., anhedonia) and impairments in cognitive function. Given the limitations of antipsychotic medication and psychotherapy in fully treating psychosis symptomatology, there has been increasing interest in other interventions such as transcranial direct current stimulation (tDCS). tDCS is a non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
(145 reference statements)
0
15
0
Order By: Relevance
“…tDCS has been used to improve functioning in patients with SSD in multiple tasks ( Chang et al , 2018 ; Gupta et al , 2018 ; Kennedy et al , 2018 ; Lee et al , 2018 ; Mellin et al , 2018 ; Mondino et al , 2018 ; Morgan and Singh, 2018 ; Sreeraj et al , 2018 ; Schülke and Straube, 2019 ); however, its effects on action-outcome monitoring have hitherto remained unexplored. Here, we provide some first insights into the effect of tDCS on the temporal prediction or monitoring of voluntary action outcomes in patients with SSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tDCS has been used to improve functioning in patients with SSD in multiple tasks ( Chang et al , 2018 ; Gupta et al , 2018 ; Kennedy et al , 2018 ; Lee et al , 2018 ; Mellin et al , 2018 ; Mondino et al , 2018 ; Morgan and Singh, 2018 ; Sreeraj et al , 2018 ; Schülke and Straube, 2019 ); however, its effects on action-outcome monitoring have hitherto remained unexplored. Here, we provide some first insights into the effect of tDCS on the temporal prediction or monitoring of voluntary action outcomes in patients with SSD.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique increasingly used for modulation of central nervous system excitability in humans (see Woods et al , 2016 , for a review). Furthermore, the use of tDCS has been shown to improve performance in various tasks and can reduce symptoms in patients with schizophrenia (for reviews, see Gupta et al , 2018 ; Kennedy et al , 2018 ; Lee et al , 2018 ; Kostova et al , 2020 ). One general assumption is that anodal tDCS increases cortico-spinal excitability and cathodal tDCS decreases it ( Nitsche and Paulus, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…These encouraging findings have led to a few small pilot studies which found that the combination of cognitive remediation plus aerobic exercise leads to differential improvement for some aspects of cognition and functioning. Similarly, based on findings that transcranial direct current stimulation (tDCS) may improve selected aspects of cognition in schizophrenia, a few small pilot studies have reported differential benefits of brief cognitive remediation plus tDCS (versus sham) interventions on trained cognitive tasks.…”
Section: Interventions For Cognitive Impairmentsmentioning
confidence: 99%
“…Therefore, we aimed to examine the effects of tDCS on the left posterior temporal cortex, thereby targeting the auditory cortex excitability, in more detail. The effectiveness of tDCS on processing in the AC is particularly interesting in the context of tDCS as a potential treatment option for electrophysiological parameters and symptoms of psychiatric diseases, e.g., lower N100 or auditory verbal hallucinations in schizophrenia ( Ford et al, 2001a , b , c , d ; Hubl et al, 2007 ; Li et al, 2016 ; Ponde et al, 2017 ; Gupta et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%